Implications of impact experiments on honeycomb shielded exterior beam-column joint - Rajeev, Anupoju; Mohotti, Damith; Shelke, Amit (Engineering structures, 2020)
As the projectile penetrates the target specimen, the impact force damages the specimen by its perforation. An application of honeycomb energy absorber leads to the proposal that minimizes the damage of the structure during its impact. A Classification map of various failure modes illustrating the target morphology is proposed. [Display omitted] •Impact resistance of the beam-column joints could be enhanced by honeycomb panels as a shielding material.•Dynamic plastification of the honeycomb core is identified as the main energy absorbing mechanism.•Beam-column joints designed for seismic events show a better impact resistance.•Core stiffness of the honeycomb influences peak acceleration and displacement.•Influence of the variant honeycomb thicknesses on the impact mitigation is investigated. The response of building structures under impact loads is a challenging subject for both numerical and analytical studies, as the available experimental data is limited. In the current research, an attempt was made to study the experimental investigation on the exterior beam-column joint against accidental and intentional impact loading. The velocity regime of the projectile was considered in the range 30–34 m/s. The response of the structural member shielded with the Aluminum honeycomb sandwich panel was compared with the unshielded beam-column joint. The target damage, failure modes, energy absorption, and evolution of cracks were examined in terms of both analytically and experimentally. Results obtained from high-speed imaging were used to obtain the projectiles incident, residual, and re-bound velocities. The application of honeycomb shielding on the seismic group specimens shows that the ballistic limit was increased by its energy absorption characteristics. It was found that they have a 22% higher ballistic limit than that of the seismic group specimens without honeycomb shielding. The shielded honeycomb sandwich panel specimens show promising results as they absorbed 49% higher impact energy than that of seismic specimens without honeycomb shielding. The current study provides a valuable reference for designing of honeycomb panels as a sacrificial material to safeguard the engineering structures against impact loads in the intermediate velocity regime.